Comportamento de reguladores do crescimento na indução de calo em gemas laterais de mandioca (Manihot esculenta Crantz). - Pinheiro, José Carlos Durans (1990)
A laboratorial experiment was carried out in Fortaleza, Ceará, Brazil in 1988 at the Federal University of Ceará, with the purpose of studying the simultaneous behavior of growth regulators and their levels for induction of callus in lateral buds of cassava (Manihot esculenta Crantz) in vitro. The basic culture medium used was the B5 medium, which was supplemented with isolated and combined levels of 2,4-D (0,1 and 2 mg/L) and benziladenine (0,1 and 2 mg/L) in the absence and presence of 0,03 mg/L giberelic acid. The treatments were the result of a 3x3x2 factorial scheme. The experlment was set in a completely randomized design with 10 replications. Environmental conditions of incubation were as follows: photoperiod of 16/8 hours (light and dark); temperature of 25±2 C, relative humidity of 74% and light intensity of 1000 lux. Following induction and development of calluses, it was concluded that the treatments presenting the most satisfactory gain of fresh matter weight from explants were those in which the AG3 was absent that is: 1 mg/L BA with 2 mg/L 2,4-D and 1 mg/L BA with 1mg/L 2,4-D. If AG3 is present in combination with 2 mg/L of BA and 1 mg/L 2,4-D the results were also satisfactory. Concerning callus induction speed, the second week was superior, when interacted with the levels of BA. Callus qualitative classification showed up that the 2,4-D and the BA when isolated, produced a light yellow callus and a friable consistency. A combination of BA and 2,4-D produced a dark yellow callus and compact consistency in the absence or in the presence of 0,03 mg/L AG3.